Acute progesterone feedback on gonadotropin secretion is not demonstrably altered in estradiol‐pretreated women with polycystic ovary syndrome - Su Hee Kim; Jessica A. Lundgren; James T. Patrie; Christine M. Burt Solorzano; Christopher R. McCartney (Physiological Reports, 2022)
Abstract Women with polycystic ovary syndrome (PCOS) demonstrate gonadotropin‐releasing hormone (GnRH) pulse generator resistance to suppression with 7 days of progesterone and estradiol administration. It remains unknown whether such women demonstrate impairments in acute progesterone negative feedback on LH pulse frequency or progesterone positive feedback on gonadotropin release. This was a randomized, double‐blind, placebo‐controlled crossover study designed to test the hypothesis that acute, progesterone‐related suppression of LH pulse frequency and progesterone‐related augmentation of gonadotropin release are impaired in PCOS. Twelve normally cycling women and 12 women with PCOS completed study. Volunteers were pretreated with transdermal estradiol (0.2 mg/day) for 3 days and then underwent a frequent blood sampling study (20:00–20:00 h), during which they received micronized progesterone (100 mg) or placebo at 06:00 h. In a second study admission, volunteers received the intervention they did not receive during the first admission, but the protocol was otherwise identical. The primary outcome measures were LH secretory characteristics and circulating gonadotropin concentrations. Exogenous progesterone did not reduce LH pulse frequency in either group. Mean LH, pulsatile LH secretion, LH pulse mass, and mean FSH increased more with progesterone compared to placebo in both groups. Although trends toward less pronounced changes in LH pulse mass and pulsatile LH secretion were observed in the PCOS group, these differences were not statistically significant. In summary, exogenous progesterone did not suppress LH pulse frequency within 12 hours in estradiol‐pretreated women, and the positive feedback effect of progesterone on gonadotropin release was not demonstrably impaired in PCOS. New & Noteworthy This study indicated that exogenous progesterone does not reduce LH pulse frequency within 12 h in women with PCOS, but progesterone acutely increased gonadotropin in these women. This study suggested that progesterone‐related augmentation of gonadotropin release may be impaired in PCOS compared to normally cycling women, but this finding was not statistically significant.